ZONASI SPASIAL SMA NEGERI DALAM PENERIMAAN SISWA BARU DI ZONA D, KABUPATEN KUNINGAN - Tusam, Mohamad; Ismail, Jalu Rafli; Sugandi, Dede (J SIG (Jurnal Sains Informasi Geografi), 2023)
The establishment of zoning for Public High Schools in Zone D of Kuningan Regency is determined by the government, with a total of 4 schools designated for this purpose. Meanwhile, data from Dapodik indicates the presence of 22 junior high schools scattered within this zone. This number does not include the count of MTs (Madrasah Tsanawiyah) under the Ministry of Religious Affairs. This situation highlights the limited capacity of Public High Schools. On the other hand, there is no clear basis for dividing the geographical areas among the schools to accommodate new students within the zone. Consequently, there is a potential for imbalance among Public High Schools in accepting new students. The research aims to determine the distribution and service areas, as well as the zoning of Public High Schools in Zone D of Kuningan Regency. Geographic Information System (GIS) methods include overlay analysis used for the distribution analysis and zoning of new student admissions. Thiessen polygon analysis is employed for service area analysis, and remote sensing techniques with a supervised classification approach are used to analyze land distribution. The results show that the distribution of Public High Schools in Zone D extends towards the west, towards the city center of Kuningan Regency, and is limited in the eastern direction, towards the border of Central Java Province. SMA Negeri 1 Cibingbin has the largest service area, covering 12,534 ha, including 6,998 ha in the Cibingbin subdistrict, 1,907 ha in Cimahi, 485 ha in Karangkancana, 3,143 hectares in Cibeureum, and a residential area of 351 ha.